THE LEADERSHIP OF PROPHET MUHAMMAD: AN ETHICAL MODELIN FACING MODERN LEADERSHIP CRISES - Anisa, Lina Nur (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2024)
This article highlights the relevance of Prophet Muhammad's leadership values in addressing modern leadership challenges, such as moral crises, corruption, and authoritarian tendencies. The study aims to analyze how the principles of transparency, accountability, and ethics demonstrated by Prophet Muhammad can be applied in contemporary leadership contexts, including government, organizations, and business sectors. The method used is a literature review and analysis of Prophet Muhammad's leadership concepts, then aligned with the needs of modern leadership. The results of this study show that applying ethical leadership values can help resolve trust deficits and injustices in society, particularly by fostering a culture of transparency and accountability. Additionally, strategies for enhancing ethical leadership in the corporate world and education are crucial for shaping future leaders with integrity. Implementing Prophet Muhammad's leadership values, such as honesty, justice, simplicity, and public participation, is proven to be relevant and effective in addressing various global challenges while offering sustainable solutions. The article recommends developing leadership education programs based on values and enhancing public accountability mechanisms as concrete steps to improve leadership systems across different sectors. Keywords: Leadership; Prophet Muhammad; Ethical Model; Modern Leadership Crises. Abstrak Artikel ini menyoroti relevansi nilai-nilai kepemimpinan Nabi Muhammad SAW dalam menghadapi tantangan kepemimpinan modern, seperti krisis moral, korupsi, dan kecenderungan otoriter. Penelitian ini bertujuan untuk menganalisis bagaimana prinsip-prinsip transparansi, akuntabilitas, dan etika yang ditunjukkan oleh Nabi Muhammad SAW dapat diterapkan dalam konteks kepemimpinan kontemporer, termasuk pemerintahan, organisasi, dan sektor bisnis. Metode yang digunakan adalah tinjauan pustaka dan analisis konsep kepemimpinan Nabi Muhammad, kemudian diselaraskan dengan kebutuhan kepemimpinan modern. Hasil penelitian ini menunjukkan bahwa penerapan nilai-nilai kepemimpinan etis dapat membantu mengatasi defisit kepercayaan dan ketidakadilan dalam masyarakat, terutama dengan menumbuhkan budaya transparansi dan akuntabilitas. Selain itu, strategi untuk meningkatkan kepemimpinan etis di dunia korporat dan pendidikan sangat penting untuk membentuk pemimpin masa depan yang berintegritas. Menerapkan nilai-nilai kepemimpinan Nabi Muhammad, seperti kejujuran, keadilan, kesederhanaan, dan partisipasi publik, terbukti relevan dan efektif dalam menghadapi berbagai tantangan global sekaligus menawarkan solusi yang berkelanjutan. Artikel ini merekomendasikan pengembangan program pendidikan kepemimpinan berdasarkan nilai-nilai dan peningkatan mekanisme akuntabilitas publik sebagai langkah konkret untuk meningkatkan sistem kepemimpinan di berbagai sektor. Kata kunci: Kepemimpinan; Nabi Muhammad; Model Etika; Krisis Kepemimpinan Modern.